Phospholipase C-β1 and schizophrenia-related behaviors - Koh, H.-Y. (Elsevier Ltd, 2013)
Abnormal expression patterns of phospholipase C-β1(PLC-β1) in specific brain areas of patients with schizophrenia, and its high genetic linkage to the disorder implicated a pathogenetical involvement of PLC-β1 signaling system. The schizophrenia-related behavioral phenotypes displayed in the mutant mice lacking PLC-β1 (PLC-β1 KO) suggested that PLCβ1-linked signaling pathways may be involved in the neural system whose function is disrupted in the pathogenesis of schizophrenia. In the brain, PLC-β1 is known to be linked to muscarinic acetylcholine receptors, metabotropic glutamatergic, serotonergic, and oxytocinergic systems. The objective of this review is to provide an overview of the current knowledge regarding these schizophrenia-related behaviors and discuss the probable ways in which PLC-β1signalling can be involved in the neural mechanisms for each behavior, which may help suggest future directions for research in this area. ？ 2013 Elsevier Ltd.
Keywords: Mus; phospholipase C beta; animal; behavior; brain; enzymology; genetics; human; metabolism; mouse; psychology; review; schizophrenia; Animals; Behavior; Brain; Humans; Mice; Phospholipase C beta; Schizophrenia; Schizophrenic Psychology